Framing human-wildlife conflict in the intermountain West: content analysis of daily newspapers to diverse audiences - Welden, Robert Foster, author; Bruyere, Brett L., advisor; Long, Marilee, committee member; Langmaid, Kim, committee member (Colorado State University. Libraries, 2017)
Connection to and appreciate for the natural world are directly linked to positive experiences participating in outdoor nature-based activities. These direct experiences have been declining over the past decade, causing concerns about the perceptions of nature by populations that don't participate in nature-based activities. This study examines framing of media coverage about human-wildlife conflicts and its implications for perception building by those audiences with less experience in the natural world. Data were collected via daily newspapers across the Intermountain West from 2010 to 2015. Results demonstrated that there were significant differences between newspapers serving larger, more urban communities and smaller, more rural communities. Findings indicate that urban audiences are exposed to messages that discourage participation in the natural world. Messages regarding human-wildlife conflict in newspapers serving larger, more urban communities should be reframed to avoid negative perceptions of nature and to motivate connection to the natural world.